1951
DOI: 10.1002/pol.1951.120060108
|View full text |Cite
|
Sign up to set email alerts
|

Hydroperoxides as initiators of emulsion polymerizations at low temperatures

Abstract: The results of emulsion polymerizations in which twenty‐eight different organic hydroperoxides were used as oxidizing agents in a standard redox recipe at 5°C. have been presented. Each hydroperoxide was tested at several different concentration levels. The hydroperoxides of chlorodiisopropylbenzene, di‐t‐butylisopropylbenzene, cyclohexylbenzene, 1,2,3,4,4a,9,10,10a‐octahydrophenanthrene, and t‐butylisopropylbenzene were found to be the most effective of the compounds tested. Oxidation mixtures, concentrates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1952
1952
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In initial production of cold GR-S in 1948 and 1949 cumene hydroperoxide (CHP) was used as the initiator (10). Wicklatz et al (11) and Fryling and Follett (1) found that certain hydroperoxides which were less soluble in water were more active and gave more rapid reactions. With the cooperation of the Hercules Powder Co., one such initiator, diisopropylbenzene monohydroperoxide (DIP), was tried in a short production experi-mental run at the Port Neches plant in November Another very important advantage was discovered.…”
Section: Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…In initial production of cold GR-S in 1948 and 1949 cumene hydroperoxide (CHP) was used as the initiator (10). Wicklatz et al (11) and Fryling and Follett (1) found that certain hydroperoxides which were less soluble in water were more active and gave more rapid reactions. With the cooperation of the Hercules Powder Co., one such initiator, diisopropylbenzene monohydroperoxide (DIP), was tried in a short production experi-mental run at the Port Neches plant in November Another very important advantage was discovered.…”
Section: Productionmentioning
confidence: 99%
“…An extreme in fast recipes is the following one, run in the laboratory. It is characterized by high soap and activator concentrations and runs to 60% conversion in only 11…”
mentioning
confidence: 99%
“…Other iron sequestering agents, such as hydrosulfide and silicate ions, and the fatty acid soaps of iron have been used. Typical recipes for both a lorv-sugar and a sugar-free system (52,55) Recent work has developed other hydroperoxides of greater polymerization-initiating pcwer (17,21,79). Rubber Reserve specifications now allow the interchangeable use of cumene hydroperoxide, diisopropylbenzene hydroperoxide, or p-menthane hydroperoxide in low temperature polymers.…”
Section: Initiation and Modificationmentioning
confidence: 99%
“…Revisiting the earlier GR-S approach, emulsion polymerization has been employed for the synthesis of 2-alkylbutadienes and offers distinct advantages for the synthesis of poly(1) and poly(1-ran-isoprene). In particular, redox pair initiators 27,28 consisting of hydroperoxides have allowed for room temperature emulsion polymerization. This is significant because although controlled radical polymerization techniques, such as RAFT [29][30][31][32][33][34] and NMP, 23,[35][36][37][38] have been successfully applied to conjugated diene systems, Diels-Alder cyclization of the diene monomer into terpenes competes with polymerization at the necessary temperatures.…”
Section: Introductionmentioning
confidence: 99%